Analysis of super-resolution via 3D structured illumination intensity correlation microscopy - Classen, Anton; von Zanthier, Joachim; Agarwal, G. S. (Optics Express, 2018)
Intensity correlation microscopy (ICM), which is prominently known through antibunching microscopy or super-resolution optical fluctuation imaging (SOFI), provides super-resolution through a correlation analysis of antibunching of independent quantum emitters or temporal fluctuations of blinking fluorophores. For correlation order m the PSF in the signal is effectively taken to the mth power, and is thus directly shrunk by the factor root m. Combined with deconvolution, a close to linear resolution improvement of factor m can be obtained. Yet, analysis of high correlation orders is challenging, which limits the achievable resolutions. Here we propose to use three dimensional structured illumination along with mth-order correlation analysis to obtain an enhanced scaling of up to m + m = 2m. Including the stokes shift or plasmonic sub-wavelength illumination enhancements beyond 2m can be achieved. Hence, resolutions far below the diffraction limit and with already low correlation orders in full 3D imaging, can potentially be achieved. Since ICM operates in the linear regime our approach may be particularly promising for enhancing the resolution in biological imaging at low illumination levels. (C) 2018 Optical Society of America under the terms of the OSA Open Access Publishing Agreement

Generation of N00N-like interferences with two thermal light sources - Bhatti, Daniel; Classen, Anton; Oppel, Steffen; Schneider, Raimund; von Zanthier, Joachim (European Physical Journal D, 2018)
Measuring the Mth-order intensity correlation function of light emitted by two statistically independent thermal light sources may display N00N-like interferences of arbitrary order N = Ma center dot 2. We show that via a particular choice of detector positions one can isolate M-photon quantum paths where either all M photons are emitted from the same source or Ma center dot 2 photons are collectively emitted by both sources. The latter superposition displays N00N-like oscillations with N = Ma center dot 2 which may serve, e.g., in astronomy, for imaging two distant thermal sources with Ma center dot 2-fold increased resolution. We also discuss slightly modified detection schemes improving the visibility of the N00N-like interference pattern and present measurements verifying the theoretical predictions.

Ghost imaging at an XUV free-electron laser - Kim, Young Yong; Gelisio, Luca; Mercurio, Giuseppe; Dziarzhytski, Siarhei; Beye, Martin; Bocklage, Lars; Classen, Anton; David, Christian; Gorobtsov, Oleg Yu; Khubbutdinov, Ruslan; Lazarev, Sergey; Mukharamova, Nastasia; et al. (Physical Review A, 2020)
Here we present the results of a classical ghost imaging experiment accomplished at an XUV free-electron laser (FEL). To perform such experiment at an FEL source each x-ray pulse was transmitted through a moving diffuser, which created a noncorrelated speckled beam. This beam was then split in two identical branches by introducing a beam splitter in the form of a transmission grating. In one of these branches the sample was positioned. We demonstrate the possibility of image formation, a double bar in our case, in the beam that has never interacted with the sample. With this experiment we extend the quantum optics methodology to the FEL community.
CRIS-Team WoS Importer:2020-02-04

Ghost Imaging at the Free-Electron Laser FLASH - Kim, Young Yong; Gelisio, Luca; Mercurio, Giuseppe; Dziarzhytski, Siarhei; Beye, Martin; Bocklage, Lars; Classen, Anton; David, Christian; Gorobtsov, Oleg Yu; Khubbutdinov, Ruslan; Lazarev, Sergey; Mukharamova, Nastasia; et al. (Optics InfoBase Conference Papers, 2021)
A classical ghost imaging experiment performed at the free-electron laser FLASH is presented. The possibility of image formation, a double bar in our case, in the beam that has never interacted with the sample is demonstrated.
CRIS-Team Scopus Importer:2023-03-27

Hanbury Brown and Twiss interference of electrons in free space from independent needle tip sources - Classen, Anton; Corrêa, Raul; Fleischmann, Florian; Semmler, Simon; Pleinert, Marc-Oliver; Hommelhoff, Peter; von Zanthier, Joachim (New Journal of Physics, 2025)
We investigate two-electron interference in free space using two laser-triggered needle tips as independent electron sources, a fermionic realisation of the landmark Hanbury Brown and Twiss interferometer. We calculate the two-electron interference pattern in a quantum path formalism taking into account the fermionic nature and the spin configuration of the electrons. We also estimate the Coulomb repulsion in the setup in a semiclassical approach. We find that antibunching resulting from Pauli’s exclusion principle and repulsion stemming from the Coulomb interaction can be clearly distinguished.
CRIS-Team Scopus Importer:2025-06-20
Keywords: electron quantum optics; fermionic Hanbury Brown and Twiss interferometer; two-electron interference

Incoherent Diffractive Imaging via Intensity Correlations of Hard X Rays - Classen, Anton; Ayyer, Kartik; Chapman, Henry N.; Roehlsberger, Ralf; von Zanthier, Joachim (Physical Review Letters, 2017)
Established x-ray diffraction methods allow for high-resolution structure determination of crystals, crystallized protein structures, or even single molecules. While these techniques rely on coherent scattering, incoherent processes like fluorescence emission-often the predominant scattering mechanism-are generally considered detrimental for imaging applications. Here, we show that intensity correlations of incoherently scattered x-ray radiation can be used to image the full 3D arrangement of the scattering atoms with significantly higher resolution compared to conventional coherent diffraction imaging and crystallography, including additional three-dimensional information in Fourier space for a single sample orientation. We present a number of properties of incoherent diffractive imaging that are conceptually superior to those of coherent method

Quantum imaging with incoherently scattered light from a free-electron laser - Schneider, Raimund; Mehringer, Thomas; Mercurio, Giuseppe; Wenthaus, Lukas; Classen, Anton; Brenner, Gunter; Gorobtsov, Oleg; Benz, Adrian; Bhatti, Daniel; Bocklage, Lars; Fischer, Birgit; Lazarev, Sergey; et al. (Nature Physics, 2018)
The advent of accelerator-driven free-electron lasers (FEL) has opened new avenues for high-resolution structure determination via diffraction methods that go far beyond conventional X-ray crystallography methods(1-10). These techniques rely on coherent scattering processes that require the maintenance of first-order coherence of the radiation field throughout the imaging procedure. Here we show that higher-order degrees of coherence, displayed in the intensity correlations of incoherently scattered X-rays from an FEL, can be used to image two-dimensional objects with a spatial resolution close to or even below the Abbe limit. This constitutes a new approach towards structure determination based on incoherent processes(11,12), including fluorescence emission or wavefront distortions, generally considered detrimental for imaging applications. Our method is an extension of the landmark intensity correlation measurements of Hanbury Brown and Twiss(13) to higher than second order, paving the way towards determination of structure and dynamics of matter in regimes where coherent imaging methods have intrinsic limitations(14).

Superresolution via structured illumination quantum correlation microscopy - Classen, Anton; von Zanthier, Joachim; Scully, Marlan O.; Agarwal, Girish S. (Optica, 2017)
We propose to use intensity correlation microscopy in combination with structured illumination to image quantum emitters that exhibit antibunching with a spatial resolution reaching far beyond the Rayleigh limit. Combining intensity measurements and intensity autocorrelations up to order m creates an effective PSF with an FWHM shrunk by the factor root m. Structured illumination microscopy, on the other hand, introduces a resolution improvement of factor 2 by use of the principle of moire fringes. Here, we show that for linear low-intensity excitation and linear optical detection, the simultaneous use of both techniques leads to a theoretically unlimited resolution power, with the improvement scaling favorably as m + root m, dependent on the correlation order m. Hence, this technique should be of interest in microscopy for imaging a variety of samples, including biological ones. We present the underlying theory and simulations, demonstrating the highly increased spatial superresolution, and point out the requirements for an experimental implementation. (C) 2017 Optical Society of America

Superresolving Imaging of Arbitrary One-Dimensional Arrays of Thermal Light Sources Using Multiphoton Interference - Classen, Anton; Waldmann, Felix; Giebel, Sebastian; Schneider, Raimund; Bhatti, Daniel; Mehringer, Thomas; von Zanthier, Joachim (Physical Review Letters, 2016)
We propose to use multiphoton interferences of photons emitted fromstatistically independent thermal light sources in combination with linear optical detection techniques to reconstruct, i.e., image, arbitrary source geometries in one dimension with subclassical resolution. The scheme is an extension of earlier work [S. Oppel et al., Phys. Rev. Lett. 109, 233603 (2012)], where N regularly spaced sources in one dimension were imaged by use of the Nth-order intensity correlation function. Here, we generalize the scheme to reconstruct any number of independent thermal light sources at arbitrary separations in one dimension, exploiting intensity correlation functions of order m >= 3. We present experimental results confirming the imaging protocol and provide a rigorous mathematical proof for the obtained subclassical resolutio